O1.06 NOVEL MARKERS OF MENINGIOMA AGGRESSIVENESS - A STUDY OF MENINGIOMA VERSUS PERITUMORAL NERVOUS TISSUE - Mazzetti, S. (Oxford University Press, 2014)
Meningiomas constitute approximately one-third of primary CNS tumors and classified by WHO in meningioma (grade I), with many histologic variants, atypical meningioma (grade II) and anaplastic meningioma (grade III). Most of them have a long survival, 1-3% are anaplastic with poor outcome and high recurrence rate and 15-20% of meningiomas are atypical with an intermediate and variable behavior. At present, only histologic grading is a reliable prognostic factor and we lack markers to identify among atypical meningiomas the most aggressive ones. For the first time in meningiomas, we propose to evaluate Lycopersicon esculentum lectin (LEA, specific for N-acetyl-D-glucosamine and N-acetyl-polylactosamine oligomers) and Aquaporin-4 (AQP4) as new factors involved in tumor invasion. LEA was chosen because it was localized in endothelial cell glycocalix in blood brain barrier (BBB) and it has been demonstrated that altered glycosilation of neoplastic cells induce vascular infiltration of cancer cells through endothelium. AQP4 is the most abundant water channel localized in the glial endfoots of the CNS and has been correlated with peritumoral oedema, that in meningioma can result as a marker of tumor invasion. The present study was performed in 20 grade I, 10 atypical and 5 anaplastic meningiomas in which a part of nervous tissue adjacent the meningioma was present on the surgical specimen. We observed a huge increase of AQP4 expression in the peritumoral nervous tissue in meningioma compared to normal nervous tissue. A thin staining in the leptomeninge and the muscolaris mucosae of the biggest vessels in tumor periphery was noticed, while tumor cells were always negative. Also in atypical meningioma AQP4 clearly define tumor boundaries. So, a minimum infiltration of nervous tissue, poorly identifiable with HE staining, could be simply visible using AQP4 staining. As for the anaplastic meningioma, which shows infiltration of nervous tissue, AQP4 has been localized also in astrocytes trapped into the tumor. In this aggressive meningioma, we found a strong LEA staining in tumor cells membrane, while grade I meningioma showed a less intense positivity. LEA expression was localized in meningothelial tumor cells and tumor vessels, as in the nervous tissue only in the endothelial cells. These observations show a role of AQP4 in peritumoral oedema and point to AQP4 as a useful marker to identify nervous tissue infiltration extension and thus meningioma aggressiveness. Moreover, LEA staining localized both in meningioma cell membranes and in the endothelial cells of the tumor vessels indicates that LEA-affinity oligomers could be implicated in adhesion and invasiveness of tumor cells. Both the glycosidic residues stained by LEA and AQP4 could be potential therapeutic targets.